PROFIL GAYA MANAJEMEN KONFLIK PADA ISTRI YANG BEKERJA DI PERKANTORAN JABODETABEK - Listia Wulan Sari; Nanda Rossalia; Zahrasari Lukita Dewi (MANASA, 2019)
Wife who works has more than one role, namely the role of wife for the husband, mother forchildren, as a housekeeper, and as a worker. The many roles and responsibilities make workingwives vulnerable to various kinds of conflicts. If the conflict experienced is not handled properly,it will have the potential to damage the existing relationship. So it becomes important for a workingwife to be able to manage her conflict well. There are five conflict management styles developedby Thomas & Kilmann (2008) based on the dimensions of assertiveness and cooperativeness,namely; Competing, Collaborating, Compromising, Avoiding, and Accomodating. This study useda quantitative method, with 128 participants with the characteristics of a wife, full-time officeworker, age range within 20-40 years old (M= 30.8; SD= 4.88), have children and live in Jakartacity, Bogor city, Depok city, Tangerang city, and Bekasi city (Jabodetabek). Conflict managementstyle is measured using the Thomas-Killman Conflict Mode Instrument (TKI) which is adapted inIndonesian. The results showed that the dominant conflict management style used by the workingwive in Jabodetabek is compromising. As well as the conflict management style that theparticipants have in each demographic category, namely participant age, length of marriage,living with nuclear family vs extended family, monthly range of income and length of work, iscompromising style.